PRINCIPLE OF LEGAL DETERMINATION - Аскеров, Зіяфат (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: conducting a detailed analysis of the formation and development of the principle of legal certainty, taking into account the diversity of opinions existing in the legal literature. Methods: analysis of conceptual ideas and legal documents on the principle of legal certainty. Results: the article provides a detailed analysis of the issues of formation and development of the principle of legal certainty, taking into account the diversity of opinions existing in the legal literature. It is noted that in the field of law and practice, the principle of legal certainty is one of the main elements of the rule of law. The European Court of Human Rights has in a number of its decisions characterized the principle of legal certainty. For example, in the judgment of the Sovtransavto Holding v. Ukraine the European Court of Justice stated that the principle of legal certainty is one of the fundamental aspects of the rule of law (rule of law). The European Court of Justice, which is the highest judicial body of the European Union, emphasized that the principle of legal certainty is an integral part of European law, therefore, all structural bodies of the European Union, as well as member states, are required to comply with this principle. Further in the article, the principle of legal certainty is considered as a constitutional principle, which for a long period of time is organically linked with the concept of the rule of law in Germany. It was from German law that this principle was introduced into international law, in particular, in the case law of the European Court of Human Rights, as well as in national legal systems. Discussion: conducting scientific discussions on the consolidation of the principle of legal certainty in any international treaty, including the European Convention on Human Rights.